Endoscopic optical coherence tomography angiography using a forward imaging piezo scanner probe. Issue 4 (30th January 2019) - Wurster, Lara M.; Shah, Ronak N.; Placzek, Fabian; Kretschmer, Simon; Niederleithner, Michael; Ginner, Laurin; Ensher, Jason; Minneman, Michael P.; Hoover, Erich E.; Zappe, Hans; Drexler, Wolfgang; Leitgeb, Rainer A.; et al.
Abstract : A forward imaging endoscope for optical coherence tomography angiography (OCTA) featuring a piezoelectric fiber scanner is presented. Imaging is performed with an optical coherence tomography (OCT) system incorporating an akinetic light source with a center wavelength of 1300 nm, bandwidth of 90 nm and A‐line rate of 173 kHz. The endoscope operates in contact mode to avoid motion artifacts, in particular, beneficial for OCTA measurements, and achieves a transversal resolution of 12 μm in air at a rigid probe size of 4 mm in diameter and 11.3 mm in length. A spiral scan pattern is generated at a scanning frequency of 360 Hz to sample a maximum field of view of 1.3 mm. OCT images of a human finger as well as visualization of microvasculature of the human palm are presented both in two and three dimensions. The combination of morphological tissue contrast with qualitative dynamic blood flow information within this endoscopic imaging approach potentially enables improved early diagnostic capabilities of internal organs for diseases such as bladder cancer. Abstract : A forward imaging endoscope providing morphological information by optical coherence tomography (OCT) as well as visualization of microvasculature by optical coherence tomography angiography (OCTA) has the potential to improve diagnosis of diseases such as bladder cancer at an early stage. In this paper, an endoscope of such kind is presented and its potential is demonstrated by presenting OCT images of the finger and OCTA images of the palm.